Resenha crítica - Oliveira, Anna Clara Viana de (Cadernos de Linguagem e Sociedade, 2014)
PASCALE, Celine-Marie (Org.). Social inequality & the politics of representation: a global landscape. Washington, DC: Sage Publications, 368 páginas, 2013.